PERAN SUPERVISI PENDIDIKAN DALAM MENINGKATKAN KINERJA GURU DI SEKOLAH - Ubabuddin Ubabuddin (Cross-border, 2018)
Supervision is not only aimed at controlling to see whether all activities have been carried out according to the plans or programs that have been outlined, but more than that. Supervision also pays attention to the state of the teacher's performance whether he is successful in teaching or not besides that supervision also pays attention to and helps the teacher in dealing with problems or weaknesses of the teacher in teaching so that he can be successful in teaching or educating. The principal as an education supervisor has the function of directing, guiding and supervising all educational activities and learning activities carried out by teachers and supported by school staff. The principal should carry out continuous monitoring of conditions and attitudes in the classroom, in the teacher's room, and at meetings with the teaching staff. The purpose is to provide assistance in solving the difficulties that are being experienced by teachers and employees as well as making improvements both directly and indirectly regarding the shortcomings, so that gradually the quality and productivity of teaching and learning activities carried out by teachers in the classroom will become better.